Fitnesz vendégek sportfogyasztási szokásai: SPORT CONSUMPTION HABITS OF FITNESSCLUB GUESTS - Bartha, Éva Judit (Közép-Európai Közlemények, 2020)
The importance of fitness providers in sports economy and the number of registered members in fitness clubs has shown a steady increase1,2. In Hungary the rate of sports activities done in fitness clubs are considered low3. We studied fitness consumers sporting and consumption habits with questionnaires. A total of 753 respondents answered the questions: 500 women and 253 men. The questionnaire completed by gym guests cover the following fields: general data, demographic characteristics, training session attendance-related habits, aspects of gym choice and the sportsperson’s willingness to spend on fitness. This questionnaire also included close- and open-ended questions, as well as Likert-scales, which assess the extent of agreement with the relevant statement4. The quantitative data obtained from the questionnaire survey were analyzed using SPSS statistical program. The results obtained through the study of training session attendance-related habits reflect, that the majority of fitness consumers responding to my questionnaire, i.e. 75% attend gym training sessions on a weekly basis. It is a significant difference as compared to the average population, 38% of which does sports with some regularity, but 62% never does any. Results reflect that tangible environment has the strongest influence on the gym choice of fitness sector consumers. Our research covers the study of spending habits of fitness consumers. Results reflect that the majority of fitness consumers in the sample (42%) spend a monthly amount of approx. HUF 6000–12000 on visiting the gym. The majority of the respondent consumers would not pay more than they pay now for fitness services. Those willing to pay higher price would spend more because of the person of the trainer. 195 of the 753 respondents (26%) would not at all pay more than the current amount for visiting the gym, and 154 people, i.e. 20% would pay at most HUF 1000 more. 270 people (36%) claimed that they would pay HUF 1000–3000 more for more beneficial conditions, 99 people (13%) would spend HUF 3000–6000 more, and 35 people (5%) would be willing to exceed this amount.